2021
DOI: 10.3389/fcvm.2021.697481
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular Morphology and Function Reference Values Derived From a Large Sample of Healthy Chinese Adults by Magnetic Resonance Imaging

Abstract: Background: Quantification of cardiac structure and function is essential for diagnostic interpretation and clinical decision making. We sought to establish cardiovascular magnetic resonance (CMR) reference values of left and right ventricular (LV and RV) morphology and function based on a large sample of healthy Chinese adults.Methods: Five hundred fifty validated healthy Chinese adults (aged 21–70 years; 323 men) free of hypertension, diabetes, and obesity were included in this study. All the subjects were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
3
6
1
Order By: Relevance
“…Moreover, in the current study, trabeculae and papillary muscles were excluded from the myocardium, which has been shown to result in larger LVEDV, LVESV, but lower LVEF and LVM. 27,28 Consistent with most previous studies, [8][9][10]19 the current study showed that males had larger biventricular volumes and higher LVM than females, even after indexing by BSA. Likewise, we also observed that EF was higher in females.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, in the current study, trabeculae and papillary muscles were excluded from the myocardium, which has been shown to result in larger LVEDV, LVESV, but lower LVEF and LVM. 27,28 Consistent with most previous studies, [8][9][10]19 the current study showed that males had larger biventricular volumes and higher LVM than females, even after indexing by BSA. Likewise, we also observed that EF was higher in females.…”
Section: Discussionsupporting
confidence: 91%
“…26 These results suggest that it is necessary to establish MRI reference ranges for different ethnicities. In addition, we also found biventricular volumes and indexed parameters in both sexes in the current study were larger than those reported in previous Chinese studies, [6][7][8][9] while the EF was slightly lower. This may be due to the fact that the subjects came from 11 provinces across the country and included a large age span, which reduces selection bias and makes the results more representative.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Our study population has been described previously [ 20 ]. All the subjects came from the local medical imaging and health screening institution, which provides high-end screening services for eligible community residents, with cardiovascular imaging as one of the key programs.…”
Section: Methodsmentioning
confidence: 99%